Competitive demands during international sprint-distance triathlon races according to the course type: The influence of cycling on subsequent running performance - Espejo, R.; Martínez-Sobrino, J.; Veiga, S. (Sports Medicine - Open, 2025)
Background Despite the great contribution of the cycling segment to the Sprint-Distance Triathlon (SDT) races, very few studies have reported the power output of elite triathletes during races. The aim of this study was to analyse the competitive demands of elite triathletes during the cycling segment of SDT races and their influence on the subsequent running segment performance, considering the different types of race courses.